Root Canal Configuration of One-rooted Mandibular Canine in an Iranian Population:An In Vitro Study - Shermin Abdollahzadeh; Hamid Reza Abdolsamadi; Shahin Kasraee; Pejman Bakianian Vaziri; Farzad Esmaeili; Shahrzad Nazari; Mohammad Vahedi (Tabriz University of Medical Sciences, 2008)
Background and aims. A perfect endodontic treatment necessitates proper understanding of the morphology of canal and pulpal variations. This in vitro study was conducted to demonstrate the internal anatomy of mandibular canine teeth in an Iranian population. Materials and methods. The samples consisted of 100 extracted mandibular permanent canines. The roots of the teeth were molded in acrylic boxes. The crowns of the teeth were cut and 2 mm cross sections were made from CEJ to the apex. Sections were examined using stereomicroscope to reveal the number and location of root canals. Results. From 100 evaluated teeth, 12 (12%) had 2 canals from which 5 had type II canal configuration and 7 (7%) had type III. 88% of the specimens had one canal and none were seen to be of type IV. Conclusion. The findings of this study emphasize the importance of dentist's knowledge of variations in root canal morphology, since leaving a canal untreated is one of the main reasons of endodontic failures. When treating mandibular canines, the existence of a second canal should be taken into consideration.